2020
DOI: 10.1101/2020.06.21.20132944
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical predictors of donor antibody titer and correlation with recipient antibody response in a COVID-19 convalescent plasma clinical trial

Abstract: Background: Convalescent plasma therapy for COVID-19 relies on the transfer of anti-viral antibody from donors to recipients via plasma transfusion. The relationship between clinical characteristics and antibody response to COVID-19 is not well defined. We investigated predictors of convalescent antibody production and quantified recipient antibody response in a convalescent plasma therapy clinical trial. Methods: Multivariable analysis of clinical and serological parameters in 103 confirmed COVID-19 co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The intermediate approach, whenever allowed by privacy regulations, is making calls to positive cases under home-based quarantine to solicit donations; given the large numbers of such cases, some of them are likely to be regular donors, and home-based convalescence suggests that they are fit enough to donate. Nevertheless, lessons from MERS ( 17 ) and preliminary evidence with COVID-19 ( 18 20 ) suggest that patients with mild symptoms may develop low-titer antibodies, making antibody titration even more important in the population-wide and home-based approaches. Plasma samples collected an average of 30 days after the onset of symptoms had undetectable half-maximal neutralizing titers in 18% of donors ( 21 ).…”
Section: Cp Donor Recruitment Strategiesmentioning
confidence: 99%
“…The intermediate approach, whenever allowed by privacy regulations, is making calls to positive cases under home-based quarantine to solicit donations; given the large numbers of such cases, some of them are likely to be regular donors, and home-based convalescence suggests that they are fit enough to donate. Nevertheless, lessons from MERS ( 17 ) and preliminary evidence with COVID-19 ( 18 20 ) suggest that patients with mild symptoms may develop low-titer antibodies, making antibody titration even more important in the population-wide and home-based approaches. Plasma samples collected an average of 30 days after the onset of symptoms had undetectable half-maximal neutralizing titers in 18% of donors ( 21 ).…”
Section: Cp Donor Recruitment Strategiesmentioning
confidence: 99%
“…Two study reported that asymptomatic healthcare workers did develop antibodies. 161,162 • Fever appears to have a consistent relationship with seropositivity and antibody titres, 29,158,160 although other symptoms such as ageusia have also been associated. 156,158…”
mentioning
confidence: 97%
“…Three studies report an association between COVID-19 symptoms and seropositivity, [156][157][158] and with higher titres of IgG, 29,159 IgA, 159 and anti-RBD and anti-S antibodies. 160…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…What other evidence underpinned the FDA’s controversial decision? The most recent version of the Cochrane living systematic review on convalescent plasma9 was available, along with more recent randomised and non-randomised studies 4101112131415. However, the only two randomised trials (189 participants in total)34 could not be combined in meta-analyses because they used different times for assessing mortality and different rating scales for clinical outcomes.…”
mentioning
confidence: 99%